Proteins in Ionic Liquids: Reactions, Applications, and Futures - Schindl, Alexandra; Hagen, Matthew L.; Muzammal, Shafaq; Gunasekera, Henadira A. D.; Croft, Anna K. (Frontiers in Chemistry, 2019)
Biopolymer processing and handling is greatly facilitated by the use of ionic liquids, given the increased solubility, and in some cases, structural stability imparted to these molecules. Focussing on proteins, we highlight here not just the key drivers behind protein-ionic liquid interactions that facilitate these functionalities, but address relevant current and potential applications of protein-ionic liquid interactions, including areas of future interest.